1992
DOI: 10.1016/0017-9310(92)90074-3
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer enhancement in the oscillating turbulent flow of a pulse combustor tail pipe

Abstract: Heat transfer rates in pulse combustor tail pipes and in other reversing, oscillating, turbulent flows have been found to be much higher than those of steady turbulent flow. To elucidate the mechanisms of the enhancement, the temperature and velocity fields, measured with two-line atomic fluorescence (TLAF) and laser Doppler velocimetry (LDV). respectively, are compared. Time-resolved wall heat fluxes and Nusselt numbers are also presented and discussed. Possible causes for the heat transfer enhancement in osc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 15 publications
3
24
0
Order By: Relevance
“…It is obvious that the distortion of the cyclic temperature curves deviated from the sinusoidal fluctuation damps with the increase in the Womersley number. Similar cyclic centerline velocity and temperature pulsations were found in experimental results of turbulent pulsating channel flow with large velocity oscillating amplitudes by Dec et al [20,47,48].…”
Section: The Effect Of Temperature Oscillation At Inletsupporting
confidence: 84%
See 3 more Smart Citations
“…It is obvious that the distortion of the cyclic temperature curves deviated from the sinusoidal fluctuation damps with the increase in the Womersley number. Similar cyclic centerline velocity and temperature pulsations were found in experimental results of turbulent pulsating channel flow with large velocity oscillating amplitudes by Dec et al [20,47,48].…”
Section: The Effect Of Temperature Oscillation At Inletsupporting
confidence: 84%
“…(16) loses its physical meaning. In this case, the section-average temperature is applied [20,40], which is defined as…”
Section: Heat Transfer Coefficients and Nusselt Numbersmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some available results are contradictory and the main question is still open: Does pulsation enhance or else degrade heat transfer compared to steady flow. Pulsating flows have been investigated in many experimental configurations: Dec et al [1], [2] have studied the impact of the pulsation frequency, pulsation amplitude, and the mean flow rate on heat transfers in the tail pipe of a pulse combustor. Spatially averaged Nusselt number computations have shown that heat transfers increase with both pulsation amplitude and frequency.…”
Section: Introductionmentioning
confidence: 99%